A New Approach to Common Coupled Fixed Point of Caristi Type Contraction on a Metric Space Endowed with a Graph - Adilakshmi, G.; N.V.Kishore, G.; Konda Reddy, N. (International Journal of Engineering and Technology, 2018)
In this paper we introduced a new notation G â€“ fg â€“Â Â contraction of Caristi type and a new edge preserving property. With help of these we proved a some coupled fixed point results for four maps endowed with a graph in a complete metric space. Also we gave an application to integral equations.Â